Identification of Gram-Negative Bacteria in the Oral Cavity of Homalopsis buccata - Ratih Novita Praja; Aditya Yudhana; Ezanti Nur Amelia; Alfian Dzaka Fadhil Ramadhan; Elham Zahrudin; Puji Aris Setiawati; Raissa Amelia Yumna; Zahrotul Andini; Roslindawani Md Nor (Media Kedokteran Hewan)
The kadut belang snake (Homalopsis buccata) is a semi-aquatic snake that can be aggressive when threatened. H. buccata is often used as a pet, a source of animal protein, and raw materials for leather crafts because of its relatively large size and unique pattern. The increasing trend of keeping reptiles as pets could increase the potential for transmission of bacteria to humans. The purpose of this study was to isolate and identify Aeromonas hydrophila, Escherichia coli, Klebsiella pneumoniae, and Salmonella sp. from H. buccata. This type of research uses the accidental sampling method as the research design. The H. buccata criteria used in this study came from wild catches and were imported during the study period. Isolation was carried out to obtain separate bacterial colonies and identification of bacteria was carried out by Gram staining and biochemical reaction tests. Identification of Gram-Negative Bacteria in the Oral Cavity showed that A. hydrophila, E. coli, K. pneumoniae, and Salmonella sp. with a percentage of 33.3%, 11.1%, 55.5%, and 22.2% in the digestive tract of H. buccata snakes in the Mojokerto City area.